Pre-lacteal feeding practice and its associated factors among mothers with children under the age of two years in Dubti town, Afar region, North East Ethiopia: a community based mixed study design - Wondmeneh, Temesgen Gebeyehu (Frontiers in Global Women's Health, 2024)
Background: Pre-lacteal feeding prevents the early initiation of breastfeeding and exclusive breastfeeding. It is understudied in Afar, a pastoral region in northeast Ethiopia. The study assessed the prevalence of pre-lacteal feeding practice and its associated factors among mothers with children under the age of two years in Dubti, North East Ethiopia.A community-based mixed-study design was employed. A systematic sampling technique was used to recruit 370 study participants for the quantitative study, while purposive sampling was used to select 17 study participants for the qualitative study. Logistic regression analysis was used to determine the association between independent variables and dependent variable. The results of logistic regression analysis were presented as an odd ratio with a 95% CI. A p-value < 0.05 was used as a cutoff point to determine statistical significance. The qualitative data were analyzed using a thematic approach. Results: Pre-lacteal feeding was practiced by 36% of mothers. Afar ethnicity (AOR = 2.5, 95% CI: 1.2-5.1), an extended family size (≥ 5) (AOR = 1.73, 95% CI: 1.02-2.9), a birth interval of less than 2 years (AOR = 2.77, 95% CI: 1.59-4.82), the first birth order of an indexed child (AOR = 3.87, 95% CI: 2.14-7.0), male-indexed children (AOR = 2.95, 95% CI: 1.67-5.2), and no antenatal care visits (AOR = 2.67, 95% CI: 1.67), or once or twice antenatal visits were significantly associated with pre-lacteal feeding practice. Breastfeeding counseling (AOR = 0.38, 95% CI: 0.2-0.7) and delivery at a health institution (AOR = 0.3, 95% CI: 0.17-0.55) were protective factors of pre-lacteal feeding practice. The most common pre-lacteal foods were dairy products, water, and certain plant species. Cultural beliefs are the main reason for practicing these pre-lacteal feedings.A significant number of study participants practiced prelacteal feeding.A public health campaign emphasizing the importance of antenatal care follow-ups should be initiated. Breastfeeding counseling and delivery in a health facility should also be strengthened. Community health education about the disadvantages of prelacteal feeding practices should be provided to reduce traditional beliefs.